2020
DOI: 10.1186/s12889-020-09256-6
|View full text |Cite
|
Sign up to set email alerts
|

Job morale: a scoping review of how the concept developed and is used in healthcare research

Abstract: Background: The job morale of healthcare staff is widely seen as an important factor for the quality of care. Yet, there are different understandings of what constitutes job morale, which hinders systematic research and comparisons. We therefore conducted a scoping review of how the concept of job morale has developed over time and how it is used in healthcare research. Methods: A scoping review was conducted to identify relevant literature. Data were gathered on study design and context, objectives, definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
(120 reference statements)
0
16
0
Order By: Relevance
“…The definition of "morale" in Western context is not clearly defined. However, employee morale is often associated with job satisfaction, feelings of well-being and an emotional connection with their workplace environment (Sabitova, et al, 2020;Mallik, et al, 2019;Bhasin, 2018;McKnight, et al 2001). Furthermore, it is suggested that management and policies such as affecting employee communications or providing support, and risk such as the potential for downsizing, have high impact on factors influencing positive or negative employee morale (Behm, 2009;Kettley, 1995).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…The definition of "morale" in Western context is not clearly defined. However, employee morale is often associated with job satisfaction, feelings of well-being and an emotional connection with their workplace environment (Sabitova, et al, 2020;Mallik, et al, 2019;Bhasin, 2018;McKnight, et al 2001). Furthermore, it is suggested that management and policies such as affecting employee communications or providing support, and risk such as the potential for downsizing, have high impact on factors influencing positive or negative employee morale (Behm, 2009;Kettley, 1995).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Wilson (2015) separated the intention to leave factors into intrinsic (level of competence, sense of accomplishment, recognition of job, autonomy and opportunities for advancement) and extrinsic (quality of supervision, support and communication from the manager) factors. Job satisfaction, considered an overlapping concept within morale (Sabitova et al. , 2020) is also often associated with burnout in healthcare (Nocon et al.…”
Section: Background Literaturementioning
confidence: 99%
“…Morale. The concept of morale, which originated in a military context [42], is a multifaceted, longitudinal, and relational experience that individuals share when they identify with and contribute to certain kinds of collective activities [43]. Morale is regarded by Weakliem and Frenkel [25] as a general term for positive feelings about the prescribed activities of the group.…”
Section: Psychological Coping Responsesmentioning
confidence: 99%